مسرحية نصوص فهم المنطوق وأهميتها في تعليم اللغة العربية - تواتي طليبة, سلوى; عروة, نوال; فريفر, خديجة (University of Eloued جامعة الوادي, 2024)
مسرحة نصوص فهم المنطوق تعتبر أداة أساسية في تعليم وتعلم اللغة العربية، خصوصا في الطور الأول من التعليم الابتدائي، تهدف هذه المسرحة إلى تنمية مهارات فهم التلاميذ(المتعلمين) للنصوص المنطوقة وتعزيز قدراتهم على التعبير اللفظي وفهم المعاني، يتم ذلك من خلال تقديم نصوص مختلفة تتنوع بين القصص والحكايات والشعر والمحادثات اليومية، مما يساعد في تنويع تجارب التلاميذ اللغوية وتوسيع آفاقهم، بالتركيز على هذه المسرحة في المرحلة الابتدائية، يمكن تحقيق تأسيس قوي لمهارات اللغة العربية لدى التلاميذ، وبناء قاعدة صلبة تمهد لتعلمهم المستقبلي؛ إذا تم تطبيقها بفاعلية فإن هذه المسرحة تعزز الفهم القرائي والكتابي، وتساهم في تعزيز التفكير النقدي وتنمية مهارات التعبير، وتنمية مهارات الاستماع والفهم مع ترسيخ القواعد النحوية والمفردات اللغوية وكذلك تنمية مهارات التخيل والإبداع وتساعد على تعزيز الثقة بالنفس، وعليه يمثل تضمين مسرحة نصوص فهم المنطوق في مناهج اللغة العربية للطور الأول من التعليم الابتدائي استثماراً أساسياً في تطوير مهارات اللغة لدى التلاميذ (المتعلمين) وتحضيرهم للمراحل التعليمية اللاحقة. The dramatization of spoken comprehension texts is considered an essential tool in teaching and learning the Arabic language, especially in the first stage of primary education. This dramatization aims to develop the skills of students (learners) understanding spoken texts and enhance their abilities to verbally express and understand meanings. This is done by presenting different texts that vary. Between stories, anecdotes, poetry, and daily conversations, which helps diversify students’ linguistic experiences and broaden their horizons. By focusing on this play in the primary stage, it is possible to achieve a strong foundation for students’ Arabic language skills, and build a solid foundation that paves the way for their future learning. If applied effectively, this dramatization enhances reading and writing comprehension, contributes to enhancing critical thinking, developing expression skills, developing listening and comprehension skills while consolidating grammatical rules and linguistic vocabulary, as well as developing imagination and creativity skills, and helps enhance self-confidence. Therefore, including dramatization of spoken comprehension texts in Arabic language curricula for the first stage of primary education are an essential investment in developing the language skills of students (learners) and preparing them for subsequent educational stages.
لسانيات عامة
Keywords: فهم المنطوق، المسرحية، اللغة العربية، التعليم، التعلم، الطور الأول من التعليم الابتدائي. تصنيف JEL: A2، I2، I21؛ I24.; Spoken comprehension; drama; Arabic language; education; learning; first stage of primary education. (JEL) Classification: A2، I2، I21؛ I24